2020
DOI: 10.3390/antibiotics9040183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxytetracycline Metabolites Cross-Reactivity with Oxytetracycline Enzyme-Linked Immunosorbent Assay (ELISA)

Abstract: Antibiotics have been successfully used for the control of several plant diseases for many years. Recently, streptomycin and oxytetracycline have been approved for the treatment of Huanglongbing (HLB) in Florida. The enzyme-linked immunosorbent assay (ELISA) is the most commonly used assay for the detection of these antibiotics because it is quick, simple, and can be used to analyze many samples at the same time. However, ELISA can react with the metabolites of the parent compound and its structurally related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The europium assay showed high cross-reactivity with the main metabolite of OTC, 4- epi -OTC (50.0 ± 3.6%), whereas α-a po -OTC and β- apo -OTC showed very low cross-reactivity (<7.5%). In our previous study, 4- epi -OTC also showed high cross-reactivity with the Acell ELISA kit, whereas α- apo -OTC and β- apo -OTC metabolite did not show any cross-reactivity below 50 ng mL −1 [ 11 ]. Our current results indicated that 4- epi -OTC, which is an epimer of OTC, forms a stable complex with europium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The europium assay showed high cross-reactivity with the main metabolite of OTC, 4- epi -OTC (50.0 ± 3.6%), whereas α-a po -OTC and β- apo -OTC showed very low cross-reactivity (<7.5%). In our previous study, 4- epi -OTC also showed high cross-reactivity with the Acell ELISA kit, whereas α- apo -OTC and β- apo -OTC metabolite did not show any cross-reactivity below 50 ng mL −1 [ 11 ]. Our current results indicated that 4- epi -OTC, which is an epimer of OTC, forms a stable complex with europium.…”
Section: Discussionmentioning
confidence: 99%
“…The ACCEL ELISA assay is very sensitive but has a narrow linear range (1.56–50 ng mL −1 ). Although the OTC ELISA assay is fast and convenient, it is very expensive [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inability to effectively prevent and control HLB remains a major hindrance to the global citrus industry's development. Currently, highaccuracy methods used for diagnosing HLB include the use of electron microscopy (Folimonova et al 2010), enzyme-linked immunosorbent assay (Hijaz et al 2020), conventional polymerase chain reaction (PCR) (Pandey et al 2021), and quantitative PCR (qPCR) (Kogenaru et al 2014). These methods are only suitable for laboratory testing, and they are time-consuming, costly, and require a high level of expertise, making them impractical for on-site detection.…”
Section: Introductionmentioning
confidence: 99%